Parathyroid carcinoma as an overlooked etiology of osteoporosis in postmenopausal women: a case report - Su, Jing; Lei, Shiqiong; Jin, Meiyuan; Hu, Hongzhi; He, Wenshan (Frontiers in Endocrinology, 2026)
Parathyroid carcinoma (PC), an extremely rare endocrine malignancy, disrupts calciumphosphorus homeostasis and lead to musculoskeletal system disorders including osteoporosis, bone pain and pathological fractures. For postmenopausal women, osteoporosis is a common disease. Therefore, secondary osteoporosis is often overlooked in this demographic. We report a 54-year-old woman presenting to Orthopedics Department due to arthralgia diagnosed with severe postmenopausal osteoporosis (PMO). After pharmacotherapy, the patient’s symptoms did not show significant improvement. Subsequent endocrine evaluation revealed hyperparathyroidism as the underlying cause. Following parathyroidectomy, histopathological evaluation confirmed the diagnosis of PC and her osteoporosis symptoms improved. This case highlights the critical need for postmenopausal women with osteoporosis to determine whether their condition is primary or secondary in nature. Moreover, the therapeutic principles for managing primary and secondary osteoporosis differ substantially. Early etiological identification is essential to optimize management.